COVID-19 pandemic and medical education: A medical student’s perspective - Abi-Rafeh, Jad; Safran, Tyler; Azzi, Alain (Canadian Medical Education Journal, 2020)
The specific impact of the COVID-19 pandemic on medical education remains elusive and evolving. Clinical teaching opportunities have become limited with the shift in focus of supervising physicians away from trainees and towards the care of the sick and vulnerable. The presence of medical students in hospitals has come to represent an added strain on vital resources, and the added risk of viral dissemination into communities has left medical students eager to help observing from only the sidelines. The present article provides a medical student’s perspective on this unique, evolving situation, and identifies several learning opportunities that medical students may reflect upon and carry forth into their careers ahead. By exploring the current and future impact of this pandemic on clerkship, pre-clerkship and post-graduate medical training, specific challenges and future direction for both medical students and educators are discussed.